A case of successful desensitization treatment with tepotinib after tepotinib-induced rash - Tomoki Tamura; Sakura Hata; Takahiro Baba; Taisaku Koyanagi; Takahiro Umeno; Kazuya Nishii; Shoichi Kuyama (Respiratory Medicine Case Reports, 2023)
Tepotinib is one of the key drugs for MET exon 14-skipping mutation-positive non-small cell lung cancer (NSCLC). The main adverse event of tepotinib treatment is edema. Rash is a rare adverse event, affecting only 0.7% of patients. We report a case of successful desensitization after skin rash caused by tepotinib. A 61-year-old male was treated with tepotinib 500 mg as second-line therapy for NSCLC with MET exon 14-skipping mutation. Treatment was discontinued on day 12 due to grade 3 erythema throughout the body. After improvement of the skin rash, he was started on 250 mg tepotinib with an oral antihistamine and topical steroid. Treatment was discontinued on day 11 due to skin rash exacerbation. One month of treatment-free follow-up showed skin rash improvement but lung carcinoma growth. Tepotinib desensitization therapy was started at a dose of 12.5 mg and gradually increased to 250 mg/day. The patient has since continued tepotinib treatment without skin rashes. Desensitization therapy may be effective for managing skin rash due to tepotinib.